TEMPERATURE MEASUREMENTS IN CATS USING DIGITAL, MERCURY AND TYMPANIC INFRARED THERMOMETERS - LIMA, B. A.; FERREIRA, L. C.; VILELA, V. L. R.; FEITOSA, T. F. (Ars Veterinaria, 2021)
With a view to reducing stress and discomfort and improving the practicality of making temperature measurements on cats, the aim of this study was to evaluate the use of a tympanic infrared thermometer (TIT), which is an easy-to-use device for measuring temperatures quickly, comfortably and more hygienically. For this, were selected 120 domestic cats living in Sousa, Paraíba, northeastern Brazil. Among them, 100 were normothermic, ten were hypothermic and ten were hyperthermic. None of them had any clinical signs of external or internal otitis. The measurements using the digital thermometer were higher than those using the TIT (P < 0.05), in the normothermic and hyperthermic cats. In the hypothermic cats, there was no difference (P ≥ 0.05) in mean values from the three types of thermometer. The values obtained using the mercury thermometer did not differ (P ≥ 0.05) from the values obtained using the other thermometers. There was a strong positive correlation in almost all the evaluations between the three thermometers, except for digital versus TIT for hyperthermic cats (r < 0.75). Because of the discrepancy between the values obtained by the TIT and the digital rectal thermometer, we suggest that further studies should be carried out in order to establish a temperature correction table for the TIT, so that it can be better used in veterinary medicine.